Mobile multimedia object management for efficient content search and exchange. (14th February 2008) - Leung, C.H.C.; Leung, T.L.Y.
In Mobile Multimedia Object (M?O) retrieval, high precision is required, as there is limited scope for browsing or relevance feedback due to limitations in both time and display size. In M?O, three kinds of data will need to be managed: raw content data; metadata for assisting non-content based searches; structured content description data to facilitate fast content based searches. These three kinds of data have to be processed and integrated to support efficient M?O management and retrieval. This paper examines methods, both automatic and semi-automatic, for capturing data that will support accurate M?O data retrieval. A data architecture and organisation structure of mobile multimedia data is presented.